Apresiasi Sastra dan Eksplorasi Diri Anak melalui Perlombaan antar Madrasah Diniyah di Desa Nambangrejo Sukorejo Ponorogo - Anni Zuhriyah; Lisma Meilia Wijayanti; Ahmad Kirom (Social Science Academic, 2025)
Organizing competitions is very important, both general competitions and religious competitions such as competitions between Madrasah Diniyah Because this competition can increase children's self-confidence, increase insight and serve as a means of channeling children's interests and talents and a forum for children's potential as a medium for evaluating each child's self This research was conducted qualitatively using a case study approach at a competition between Madrsah Diniyah in Nambangrejo Village, Sukorejo Ponorogo subdistrict.